St. Louis Cardinals - Lajiness, Katie (2019)
"Students will love learning about the St. Louis Cardinals in this high-interest title! Text covers the team's history, memorable wins, star players, and important coaches. Features include table of contents, fun facts, team stats, timeline, glossary, and index. Aligned to Common Core standards and correlated to state standards."--
Major League Baseball -- A Winning Team -- Busch Stadium -- Then and Now -- Highlights -- Famous Managers -- Star Players -- Final Call -- Through the Years -- Glossary -- Online Resources -- Index.
Includes index.
Ages 7-10
Keywords: Major League Baseball (Organization) -- Juvenile literature; St. Louis Cardinals (Baseball team) -- Juvenile literature; St. Louis Cardinals (Baseball team) -- History; Baseball teams -- United States -- History -- Juvenile literature; Sports teams -- Juvenile literature